Model-Based Evaluation of HangAmDan-B1 and Afatinib Combination Therapy in HCC827 Xenograft Mice with Resistance to Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor - Sung-yoon Yang; Lien Thi Ngo; Soyoung Lee; Hwi-yeol Yun; Tham Thi Bui; Dong-Hyeon Kim; Jung-woo Chae; Sojung Park (Pharmaceuticals)
Objectives: HangAmDan-B1 (HAD-B1), a blended herbal mixture, has been investigated as an adjuvant therapy with afatinib (AFT) to treat non-small lung cancer (NSCLC). Although preclinical studies demonstrated promising synergistic results, clinical trials have not yet confirmed the expected benefits. This study aims to quantitatively examine the exposure–response relationship and synergistic interactions through pharmacokinetic/pharmacodynamic (PK/PD) modeling. Methods: A PK/PD model was established and validated based on tumor growth profiles from a xenograft mouse study of gefitinib-resistant HCC827. Model-based simulations were performed to predict and assess therapeutic effects across different treatment groups. Results: The PK/PD model confirmed HAD-B1 enhances the potency of AFT by 1.45-fold. Model-based simulations predicted that combination treatment maintains a lower tumor size compared to AFT monotherapy. Conclusions: This study quantitatively demonstrated the synergistic interaction between HAD-B1 and AFT. The developed PK/PD model provides insights into potential dosing strategies to treat NSCLC resistant to EGFR-TKIs. Further clinical trials are warranted to validate these findings and refine dosing strategies to improve therapeutic outcomes.